Pengaruh Pengawasan Terhadap Kinerja Pegawai Di Kantor Kecamatan Bontonompo Kabupaten Gowa - Sriwahyuni, Ita; Said, Alimuddin; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
The purpose of this study was to find out how the form of supervision and its effect on employee performance. This study was conducted at the Bontonompo District Office in Gowa Regency. Data collection techniques were the study of literature, field studies such as observation, documentation, interviews, and questionnaires. Data analysis techniques were descriptive analysis techniques and simple linear regression analysis techniques. The total population in the study were all employees of the Bontonompo District Office of Gowa Regency as many as 30 employees. The withdrawal of the sample used the saturation sampling technique. Based on the results of statistical analysis of the summary model table, explaining the magnitude of the correlation or relationship (R) value was 0.793. From the influence of the independent or supervisory variable (X) on the dependent variable of employee performance (Y) shown by the Adjusted R Square value of 0.615, it meant that 61% of the influence of the independent or supervisory variable (X) on the employee performance dependent variable (Y) in the Bontonompo District Office Gowa Regency, from the output results was a good level.